The New Encyclopedia Britannica Volume 12 - Gwinn, Robert P et al (Encyclopedia Britannica Inc., 1992)
The Encyclopedia Britannica combines today's current topics with over 238 years of expertise and delivers more depth, breadth, and information than other encyclopedia. Readers can access quick facts or immerse themselves in detailed articles on almost any subject imaginable while enjoying the vivid and beautiful images of art, geography, science, sports, and much more.
Keywords: Encyclopedia-Literature (World)-Reference-Non fiction